Increased fat synthesis and limited apolipoprotein B cause lipid accumulation in the liver of broiler chickens exposed to chronic heat stress. (27th February 2019) - Lu, Z; He, X F; Ma, B B; Zhang, L; Li, J L; Jiang, Y; Zhou, G H; Gao, F
ABSTRACT: Chronic heat stress can enhance fat synthesis in broilers, and excessive triglyceride (TG) synthesized by the liver needs to be transported to extrahepatic tissues by very low density lipoprotein (VLDL) otherwise will accumulate in the liver, which may even result in hepatic steatosis. To investigate the molecular mechanisms by which chronic heat stress enhances fat synthesis and results in lipid accumulation in the liver of chickens, 144 broilers (Arbor Acres, 28-day-old) were randomly allocated to the normal control (NC, 22°C), heat stress (HS, consistent 32°C), or pair-fed (PF, 22°C) groups for a 14-D trial. The 7 D of heat exposure significantly increased the respiratory rate, relative weight of abdominal fat, the levels of glucose, TG, corticosterone, insulin, and VLDL in plasma, as well as the levels of TG, total cholesterol, acyl-CoA carboxylase (ACC), and fatty acid synthase (FAS) in the liver, and mRNA expression levels of carbohydrate response element-binding protein (ChREBP), ACC, FAS, and microsomal triglyceride transfer protein (MTTP) in comparison with the other 2 groups. After 14 D of heat exposure, the relative weights of abdominal fat and liver and levels of TG and FAS in the liver were significantly higher in the HS group than in the other 2 groups, and there were no significant differences in the respiratory rate, plasma corticosterone concentration, apolipoprotein B (ApoB) level in the liver, and mRNA expression levels of key genes of fat synthesis among the 3 groups. In conclusion, chronic heat exposure activated LXRα pathway and enhanced fat synthesis in the liver after 7 D of heat exposure. After 14 D of heat exposure, heat-stressed broilers exhibited an adaptation to the high temperature in parameters of stress and fat synthesis gene expression levels. Moreover, chronic heat stress resulted in lipid accumulation in the liver of broilers, which is probably because the limited ApoB was not enough to transport the excessive TG synthesized by the liver in chronic heat-stressed broilers.